PERKEMBANGAN STATISTIKA DAN PENERAPANNYA DI BERBAGAI BIDANG - Khairil A. Notodiputro (FMIPA Universitas Papua, 2002)
Statistic is a meaning of numbers of data analyses that can be used to describe the object or phenomenon faced. For example, the growth of population in a district or area can be analysed or predicted using variabel of birth rate, mortal rate, imigration and emigration rate. The quality of human resources can be reviewed from variabel of life standart index.(mutu standard index). On the other hands, statistica refers to a disipline of collecting, analising and as a skill of summerizing the analysis being mad.